2010
DOI: 10.1242/jcs.074161
|View full text |Cite
|
Sign up to set email alerts
|

Basal body movements orchestrate membrane organelle division and cell morphogenesis inTrypanosoma brucei

Abstract: SummaryThe defined shape and single-copy organelles of Trypanosoma brucei mean that it provides an excellent model in which to study how duplication and segregation of organelles is interfaced with morphogenesis of overall cell shape and form. The centriole or basal body of eukaryotic cells is often seen to be at the centre of such processes. We have used a combination of electron microscopy and electron tomography techniques to provide a detailed three-dimensional view of duplication of the basal body in tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(153 citation statements)
references
References 46 publications
5
148
0
Order By: Relevance
“…To more clearly identify this tendrillar projection, extracted cells were labeled with antiTbPLK antibodies, negatively stained, and then visualized by electron microscopy (EM). In dividing cells, the new MtQ is initiated on the anterior side of the new basal body (Lacomble et al, 2010). At early stages of the cell cycle the new MtQ was labeled with TbPLK in a pattern similar to that seen using immunofluorescence ( Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…To more clearly identify this tendrillar projection, extracted cells were labeled with antiTbPLK antibodies, negatively stained, and then visualized by electron microscopy (EM). In dividing cells, the new MtQ is initiated on the anterior side of the new basal body (Lacomble et al, 2010). At early stages of the cell cycle the new MtQ was labeled with TbPLK in a pattern similar to that seen using immunofluorescence ( Fig.…”
Section: Resultssupporting
confidence: 58%
“…The first stage of this process is maturation of the probasal body, which gains the capacity to nucleate a new flagellum (Lacomble et al, 2010). This maturation can be tracked with antibodies against trypanosome basal body component (TBBC) protein, a coiled coil protein shown to associate selectively with mature basal bodies (Dilbeck et al, 1999;Absalon et al, 2008).…”
Section: Tbplk Depletion Does Not Affect Basal Body Duplication or Mamentioning
confidence: 99%
See 1 more Smart Citation
“…The flagellar pocket region also appeared normal in CC2D RNAi cells. Previous reports suggested that a new flagellum and a new FAZ play important roles in flagellar pocket organization, basal body positioning and segregation (Absalon et al, 2008;Kohl et al, 2003;Lacomble et al, 2010). Whereas elongation of the new flagellum, with its distal end anchored to the old flagellum, pushes the new basal body away to the posterior end of the cell, the new FAZ might restrain the segregation and hold the new basal body in place.…”
Section: Discussionmentioning
confidence: 99%
“…The mature basal body seeds the growth of the flagellum. The pro-basal body, initially constructed anterior to the mature basal body, migrates to the posterior side of the mature basal body upon maturation, thus allowing the construction of a new flagellum posterior to the old flagellum (Lacomble et al, 2010). The basal bodies also physically link to the kinetoplast (aggregated mitochondrial DNA) and drive kinetoplast division during the cell cycle (Ogbadoyi et al, 2003;.…”
Section: Cc2d Depletion Inhibits Basal Body Segregationmentioning
confidence: 99%